COMPARATIVE ANALYSIS OF MACROSCOPIC VS MICROSCOPIC MEASUREMENT CRITERIA OF INDUCED TOOTH MOVEMENT - Moreira, José Roberto Alves; Cuoghi, Osmar Aparecido; de Mendonça, Marcos Rogério; Consolaro, Alberto; Martins-Ortiz, Maria Fernanda; Brandão, Henrique Barcelos; Gandini Junior, Luiz Gonzaga; Pinto, Ary dos Santos (Seven Editora, 2026)
This study aims to compare microscopic changes in the periodontal ligament (PDL) thickness with macroscopic tooth displacement in a rat model of orthodontic tooth movement. Seventy rats were divided into two experimental groups (GI and GII, N = 30 each) and a control group (GC, N = 10). GI received continuous orthodontic force with a coil spring appliance (50 cN), while GII received interrupted forces, applied in four-day cycles. The experimental groups were randomly subdivided (N = 10 per subgroup), and euthanized on days 8, 16, and 24 post-appliance installation. The distance between the distal face of the last molar and the mesial face of the first molar was measured to assess macroscopic displacement, calculated by subtracting the measurements of the unmoved side. PDL thickness was measured microscopically, and thickness changes (TC) were calculated by subtracting the mean PDL thickness of the control group. Pearson correlation analysis revealed a strong positive correlation between PDL TC and tooth displacement across all time points (r > 0.83). No significant differences in macroscopic displacement were observed between GI and GII at any time point (p > 0.05), however, the PDL TCs were significantly smaller in GI at all time points (p < 0.02), suggesting faster bone formation in this group. Microscopic changes in PDL TC correlated strongly with macroscopic tooth displacement in our rat model. Bone formation was achieved faster in the continuous force group compared to the interrupted force group while the final tooth displacement was similar.DOI: https://doi.org/10.56238/sevened2026.008-015